The Conciliator in the Constituent Assembly : José Honório Rodrigues’ Analysis of the 1823 Constituent Assembly. - Alves Junior, Paulo (Em Perspectiva, 2024)
The article aims to recover the analysis that José Honório Rodrigues makes of José Bonifácio's participation in the Constituent Assembly of 1823. José Bonifácio de Andrada e Silva, appears as an important character for understanding the direction that the Constituent Assembly, dismissed by D. Pedro I, he had. Furthermore, José Honório characterizes him as a great defender of “national unity” and a great conciliator in defending the Nation’s interests.